Semiconducting behavior of pure copper in alkaline solutions - A. Fattah-alhosseini; M.K. Keshavarz; A. Masomi; S. Marianaji (Egyptian Journal of Petroleum)
The corrosion resistance of passive film is correlated with its semiconducting properties, which can be measured by the Mott–Schottky analysis in high frequency domain. In this study, the semiconducting behavior of passive films formed on pure copper in aqueous NaOH solutions was investigated using Mott–Schottky analysis. The polarization curves suggested that pure copper shows comparable passive behavior in NaOH solutions with different concentrations. Also, the potentiodynamic polarization curves showed corrosion current densities reduction with decrease in concentration of NaOH solutions. In Mott–Schottky analysis, no evidence of n-type semiconducting behavior was found, indicating that oxygen vacancies and copper interstitials do not have a significant population density in the passive film. Also, this analysis indicated that with the decrease of NaOH concentration in the solution, the acceptor density of passive films increases.